Association of daily coffee consumption with cardiovascular health – results from the UK Biobank. (14th October 2021) - Simon, J; Fung, K; Raisi-Estabragh, Z; Aung, N; Khanji, M Y; Kolossvary, M; Merkely, B; Munroe, P B; Harvey, N C; Piechnik, S K; Neubauer, S; Petersen, S E; et al.
Abstract: Background: There are conflicting reports on the association of coffee consumption with cardiovascular (CV) health. The UK Biobank is a prospective cohort study including data for half a million middle-aged individuals. Purpose: We studied the association of daily coffee consumption with all-cause and CV mortality, and incidence of the major CV diseases in the UK Biobank. In a subgroup of participants who underwent cardiovascular magnetic resonance (CMR), we evaluated the association between regular coffee intake and cardiac structure and function parameters. Methods: UK Biobank cohort of participants without clinically manifested heart disease at the time of recruitment were included. Regular coffee intake was categorized into 3 groups: zero, light-to-moderate (0.5–3 cups/day) and high (>3 cups/day) coffee drinkers. We estimated association of daily coffee consumption with incident outcomes using multivariable Cox-regression models (median follow-up of 11 years) and, in the subset with CMR data, with left and right ventricular (LV, RV) end-systolic and end-diastolic volumes, LV mass, and LV/RV stroke volume using multivariable linear regression. Models were adjusted for potential confounders and mediators, including: age, sex, non-European ethnicities, body mass index, smoking, physical activity, Townsend deprivation index, alcohol, meat, fruit and vegetable intake, hypertension, diabetes mellitus, and cholesterol level. Results: We included 468, 629 individuals (mean age 56.2±8.1 years, 44.2% male). Among them, 22.1% did not consume coffee on a regular basis, 58.4% had 0.5–3 cups per day and 19.5% had >3 cups per day. After adjustment for potential confounders and mediators, compared to non-coffee drinkers, light-to-moderate coffee drinking was associated with lower risk of all-cause mortality (HR=0.88, p<0.001), CV mortality (HR=0.83, p=0.006), and incident stroke (HR=0.79; p=0.037). CMR data were available in 30, 650 participants. In multivariable analysis, compared to non-coffee drinkers, both the light-to-moderate and high coffee consuming categories, were associated with significantly increased LV and RV ventricular end-systolic (β=0.91 and 1.64 for LV and 1.10 and 1.72 for RV), end-diastolic (β=2.21 and 3.28 for LV and 2.24 and 3.35 for RV) and stroke volumes (β=1.31 and 1.64 for LV and 1.15 and 1.63 for RV), as well as greater LV mass (β=0.78 and 1.64; all p<0.001). Conclusion: In this large study of the UK Biobank population, regular coffee consumption of up to 3 cups per day was associated with favorable cardiovascular outcomes, in particular, decreased all-cause and CV mortality and stroke incidence. Regular coffee consumption was also associated with a pattern of CMR metrics in keeping with the reverse of age-related cardiac alterations. Funding Acknowledgement: Type of funding sources: None.